Effectiveness of the Beneish Model in Detecting Financial Statement Manipulations - Golec, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The aim of this study is to verify whether Beneish M‑Score model can be useful in detecting Polish companies involved in earning management practices that lead to adverse or disclaimer of auditors’ opinion. The sample covers 24 pairs of firms listed on Warsaw Stock Exchange or New Connect (alternative market). The findings generally indicate that with –2.22 point cut‑off the model was able to identify 67% of manipulators and 75% non‑manipulators correctly. The accuracy of the model improved from 71% to 75% after shifting the cut‑off point to –1.98. Another observation was that high changes in M‑Score values turned out to be better indicator of manipulation and the classification based on 35% change in year‑to‑year values reached 85% accuracy.